INTEGRATING QUR’ANIC AND HADITH VALUES IN PRIMARY CIVIC EDUCATION: IMPLEMENTATION, CHALLENGES, AND SHALIH–MUSLIH - Syaicha Akmala; Mufatihatut Taubah (Yayasan Adra Karima Hubbi, 2025)
Character education plays a crucial role in responding to contemporary challenges such as declining integrity and weakening social cohesion. This study aims to examine teachers’ understanding of social and civic values rooted in the Al-Qur’an and Hadith and to explore how these values are implemented in the teaching and learning process at the elementary school (SD/MI) level. In addition, the study investigates the challenges and future prospects of developing Shalih–Muslih character among students. A descriptive qualitative approach was employed, with data collected through semi-structured interviews involving two elementary school classroom teachers. The findings reveal that teachers perceive social and civic values as shared responsibilities and moral obligations grounded in the Islamic principle of ta’awun, as stated in QS. Al-Maidah verse 2. The implementation of these values is primarily carried out through role modeling, habituation, and authentic action-based learning activities, which encourage positive attitudes and active student participation. However, the integration of social and civic values in learning faces several challenges, including differences in emphasis between religious and general curricula and the limited application of holistic pedagogical approaches. Despite these constraints, teachers recognize significant opportunities to strengthen character education through curriculum integration and improved instructional strategies. This study concludes that Islamic education should aim to develop students who are Shalih (spiritually virtuous) and Muslih (socially transformative), enabling them to contribute positively to social life and national development.